On the path to trade liberalization: Political regimes in international trade negotiations - Florian Mölders (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
The number of free trade agreements has increased substantially since 1980 despite efforts to promote multilateral trade liberalization. While there is evidence on the determinants of FTA formation, still little is known on the processing of trade agreements, particularly regarding the pre-implementation duration. This paper fills the research gap by using event data on the proposal, the negotiation, the signing, and the implementation of trade agreements. Duration analysis is employed to examine the connection between regime types and the lengths of the negotiation and the ratification stages. The results support the claim that higher levels of democratization and political constraints are associated with delays in the implementation of an agreement. This is primarily observable in the ratification stage. Moreover, I detect significantly prolonged negotiation talks and ratifications if the European Union participates.
Keywords: F13; 330; Free trade agreements; International cooperation; Duration analysis